Estimating economic and environmental trade-offs of managing nitrogen in Australian sugarcane systems taking agronomic risk into account. (1st October 2018) - Kandulu, John; Thorburn, Peter; Biggs, Jody; Verburg, Kirsten
Abstract: Use of chemical agricultural inputs such as nitrogen fertilisers (N) in agricultural production can cause diffuse source pollution thereby degrading the health of coastal and marine ecosystems in coastal river catchments. Previous reviewed economic assessments of N management in agricultural production seldom consider broader environmental impacts and uncertain climatic and economic conditions. This paper presents an economic risk framework for assessing economic and environmental trade-offs of N management strategies taking into account variable climatic and economic conditions. The framework is underpinned by a modelling platform that integrates Agricultural Production System sIMulation modelling (APSIM), probability theory, Monte Carlo simulation, and financial risk analysis techniques. We applied the framework to a case study in Tully, a coastal catchment in north-eastern Australia with a well-documented N pollution problem. Our results show that switching from managing N to maximise private net returns to maximising social net returns could reduce expected private net returns by $99 ha −1, but yield additional environmental benefits equal to $191 ha −1 . Further, switching from managing N to maximise private returns in years with the highest profit potential (hereafter, good years ) to maximising mean social net returns could reduce expected private profits in good years by $277 ha −1, but yield additional environmental benefits equal to $287 ha −1 . We contend that it is essential to incorporate farmer risk behaviour and environmental impacts in analyses that inform policies aimed at enhancing adoption of management activities for mitigating deterioration of the health of coastal and marine ecosystems due to diffuse source pollution from agricultural production. Highlights: Applying socially optimum N rate can yield environmental benefits worth $191 ha −1 . Environmental benefit of socially optimum N rate outweigh economic cost by $92 ha −1 . Incorporating risk behaviour and environmental impacts in N decisions is crucial. N decisions need to take variable economic and climatic conditions into account. Incentive policies should be based on quantified economic and environmental impacts.